X-Ray fluorescence (XRF) of discrete samples from IODP Hole 389-M0102A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Results of X-Ray fluorescence (XRF) on discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. During the onshore phase a set of solid-phase samples were taken from the work halves of core sections, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. Bulk samples were subsequently freeze-dried, ground and homogenized to a fine powder (<20 μm particle size) by ECORD Science Operator staff using a pestle and an agate mortar or a ball mill. For elemental composition analyses an aliquot of approx. 4 g (±0.2 g) powdered and homogenized sample was weight into a plastic cuvette consisting of a Mylar foil bottom covered with polypropylene film ad compacted twice with a force of approx. 25 kg/cm3 on a plastic piston to obtain a smooth surface. Elemental concentrations were then determined by ED-XRF spectroscopy utilizing a PANalytical Epsilon 3-XLE benchtop ED-XRF spectrometer operated in the MARUM sediment geochemistry laboratory. Quality flag "#0" indicates the measurements extquotesingle result was below detection limit. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025